Investigation of apelin expression in endometriosis - Ozkan, Zehra Sema; Cilgin, Hasan; Simsek, Mehmet; Cobanoglu, Bengu; Ilhan, Necip (My University, 2013)
Background: Apelin is a mitogenic peptide; it has functions in vessel formation and cell proliferation. In this study we aimed to evaluate the serum and tissue levels and local expression pattern of apelin in eutopic and ectopic endometrium from patients with and without endometriosis and to compare the proliferative and secretory phase differences. Methods: Thirty women with endometriosis and 15 women without endometriosis undergoing surgery for benign indications as control group were included in the study. Serum and tissue concentrations and proliferative and secretory phase expression patterns of apelin were evaluated in the ectopic and eutopic endometrium using immunoassay and immunohistochemistry methods. The results were compared with Mann-Whitney U test. The p-values smaller than 0.05 were considered as statistically significant. Results: Apelin expression was detected in eutopic and ectopic endometrium of women with endometriosis and endometrium of control group. Intense immunoreactivity of apelin was observed in glandular cells of eutopic and ectopic endometrial tissues of women with endometriosis and endometrium of control group during secretory phase (p<0.01). In both groups, tissue concentrations of apelin were higher than of the serum (p=0.03) but, there were no significant differences between the two groups for tissue and serum concentrations of apelin. Conclusion: Apelin expression showed cyclic changes in eutopic and ectopic endometrium. Its expression may be related to menstrual changes of angiogenesis in endometrium of women. © 2013 Avicenna Research Institute.
Keywords: Angiogenesis; Apelin; Endometriosis; Endometrium; Expression pattern